أبنية الجمع عند البصريين وما يقابلها في اللغتين العربية والانجليزية دراسة وصفية تقابلية: Basrai Plural Structures & their counterparts in Arabic & English: A Descriptive & Contrastive study - Al Abdullah, Murad Hameed (SIBAWAYH Arabic Language and Education, 2021)
Selecting the topics of Plural is considered an important one in contrastive studies to find out affinities and discrepancies across Arabic & English. This study conducts a descriptive and inductive approach to examine plurality in Arabic and English. The most important techniques and structures in Arabic were highlighted. The plural system falls into two types: regular with its structural mechanisms the the irregular with its forms and categories then, the study examined plurality in English via investigating its structures and mechanisms. There are also regular and irregular forms. Plurals affect the formatting of the word in terms of their phonetic forms and their structures. The final stage concerns the contrastive analysis across Arabic and English to find out similarities and differences regarding plurality.